Comparative Analysis of Rhizospheric Bacteria Associated with Four Medicinal Plants - Jyotirmayee, B; Mahapatra, Sujata; Mahalik, Gyanranjan (Asian Journal of Biological and Life Sciences)
Rhizosphere microbes contribute greatly to the growth, development and functioning of plants and trees. Microbes living in the rhizospheric area depend on the soil conditions and the products released by the plants. The objective of this work is to study microbes present in the rhizospheric region of Amla (Phyllanthus emblica L.) soil. A comparative study was also conducted among Amla (Phyllanthus emblica L.), Guava (Psidium guajava L.), Jamun (Syzygium cumini (L.) Skeels) and Neem (Azadirachta indica A. Juss.) growing on the same soil. The work indicates that the plant and its rhizosphere may have some effect on microbial diversity. The study on the rhizosphere of amla plant soil was undertaken to have a better understanding of the microbes present on the rhizosphere. Different microbes present in the Phyllanthus emblica (Amla) rhizospheric region. A large variation can be found in many other bacterial species. Details study in this regard will bring many interesting facts about plant-microbe interaction.
Keywords: Azadirachta indica; Bacteria; Microbial; Phyllanthus emblica; Rhizospheric; Syzygium cumini